In vitro-derived platelets: the challenges we will have to face to assess quality and safety. (17th August 2020) - Mookerjee, S.; Foster, H. R.; Waller, A. K; Ghevaert, C. J.
Abstract: Platelet transfusions are given to patients in hospital who have a low blood platelet count (thrombocytopenia) either because of major bleeding (following trauma or surgery) or because the bone marrow production of platelets is impaired often due to chemotherapy, infiltration with malignant cells, fibrosis or genetic disorders. We are currently entirely reliant on blood donors as a source of platelets in transfusion medicine. However, the demand for platelets continues to rise, driven by an aging population, advances in medical procedures and ever more aggressive cancer therapies, while the supply of blood donors continues to remain static. In recent years, several groups have made major advances toward the generation of platelets in vitro for human transfusion. Recent successes include results in both generating mature human megakaryocytes as well as in developing bioreactors for extracting platelets from these megakaryocytes. Platelets made in vitro could address several issues inherent to platelets derived from blood donors – the ability to scale up/down more flexibly according to demand and therefore less precarious supply line, reduction of the risk of exposure to infectious agents and finally the possibility of engineering stem cells to reduce immunogenicity. Here we define the quality control tools and suggest measures for implementation across the field for in vitro platelet genesis, to aid collaboration between laboratories and to aid production of the burdens of proof that will eventually be required by regulators for efficacy and biosafety. We will do this firstly, by addressing the quality control of the nucleated cells used to make the platelets with a particular emphasis to safety issues and secondly, we will look at how platelet function measurement are addressed particularly in the context of platelets derived in vitro.